KAJIAN PSIKOLOGI SASTRA DAN NILAI KARAKTER PADA PUISI JANTE ARKIDAM KARYA AJIP ROSIDI - Syahda Deviana Salsabila (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2022)
This study aims to describe: (1) the structural aspects of Ajip Rosidi's Jante Arkidam Poem (2) the psychological aspects of Jante Arkidam's Poem (3) The author's psychology (4) The psychology of the reader. This research method is descriptive qualitative using the approach of Literary Psychology. The source of this research data is Ajip Rosidi's Jante Arkidam published by cupumanik publisher in 1967. The data of this study are intrinsic elements, extrinsic elements and psychology. The data collection techniques used are document techniques, listening techniques and note-taking techniques. In this study, researchers used content analysis techniques as data analysis techniques. The results of this study show that: 1) aspects of intrinsic elements in Poetry include; (a) stanzas and arrays, (b) rhymes/rhythms, (c) diction/word choice, (d) imagery/imagery, (e) majas/stylistics. 2) aspects of extrinsic elements include; (a) the license granted by the author. 3) the representation of the figure of Jante Arkidam. These three structures influence the behavior, mindset, and representation of the figure jante Arkidam in the poem Jante Arkidam by Ajip Rosidi.